2023
DOI: 10.1002/chem.202301316
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Halide Ion‐Pair Binding in Conformationally Dynamic Halogen Bonding Heteroditopic [2]Rotaxanes

Abstract: A series of heteroditopic halogen bonding (XB) [2]rotaxanes were prepared via a combination of passive and active metal template-directed strategies. The ability of the [2]rotaxanes to bind alkali metal halide ion-pairs was investigated by extensive 1 H NMR titration studies, wherein detailed analysis of cation, anion and ion-pair affinity measurements indicate dramatic positive cooperative enhancements in halide anion association upon either Na + or K + pre-complexation. This study demonstrates that careful c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…It was found that these systems selectively bind LiCl over LiBr or LiI. Follow-up studies were reported to extend the applicability of the approach to other alkali metal halides [98,99]. It is hoped that the DFT computational results presented in this work provide a foundation and motivation to help expand research in the field of halogen bonds.…”
Section: Future Perspectivesmentioning
confidence: 78%
“…It was found that these systems selectively bind LiCl over LiBr or LiI. Follow-up studies were reported to extend the applicability of the approach to other alkali metal halides [98,99]. It is hoped that the DFT computational results presented in this work provide a foundation and motivation to help expand research in the field of halogen bonds.…”
Section: Future Perspectivesmentioning
confidence: 78%